Rancang Bangun Aplikasi Augmented Reality Sebagai Pembelajaran Metamorfosis Kupu-Kupu - Arwa, Briliana Wijdani; Sejati, RR Hajar Puji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Observing the butterfly transformation process directly, apart from books, can enrich the learning experience and make it more interesting. However, due to the challenges of direct observation, technological innovation is needed to support learning. The aim of this research is to use Augmented Reality (AR) technology as a learning tool for butterfly metamorphosis. In the context of learning, the changes in butterfly shape will be presented through three-dimensional media using an AR-based Android application. Information related to butterfly development will also appear when the 3D object is detected on the marker. The method used in developing this AR application is through marker-based tracking, which uses markers to identify objects. It is hoped that with this application, learning about butterfly metamorphosis can become more engaging and interactive for students.